Active gas seepage in western Spitsbergen fjords, Svalbard archipelago: spatial extent and geological controls - Rodes, Nil; Betlem, Peter; Senger, Kim; Römer, Miriam; Hodson, Andy; Liira, Martin; Birchall, Tom; Roy, Srikumar; Noormets, Riko; Smyrak-Sikora, Aleksandra; Olaussen, Snorre; Bohrmann, Gerhard (Frontiers in Earth Science, 2023)
This study presents the first systematic observations of active gas seepage from the seafloor in the main fjords of western Spitsbergen in the Svalbard archipelago. High-resolution acoustic water column data were acquired throughout two research cruises in August 2015 and June 2021. 883 gas flares have been identified and characterized in Isfjorden, and 115 gas flares in Van Mijenfjorden. The hydroacoustic data indicate active fluid migration into the water column. Interpretation of 1943 km of regional offshore 2D seismic profiles supplemented the water column and existing gas geochemical data by providing geological control on the distribution of source rocks and potential migration pathways for fluids. In the study area, bedrock architecture controls the fluid migration from deep source rocks. Faults, high permeability layers, heavily fractured units and igneous intrusions channel the gas seepage into the water column. The observations of gas seepage presented in this study are an important step towards the assessment of how near-shore seepage impacts upon the carbon budget of Svalbard fjords, which constitute globally recognized early climate change warning system for the High Arctic